Pendidikan Pranatal dalam Perspektif Filsafat Ilmu - Humaidah Humaidah; M. Yunus Abu Bakar (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
For parents who have children, it is a great gift and trust from Allah SWT. Therefore, parents have a big responsibility to educate their children optimally. This study is based on concerns about the increasingly uncontrolled flow of information and that many children are falling into negative and anarchic things. As parents we have a very important task in implementing prenatal education as the first form of education for the younger generation. However, problems often arise when parents are less aware of the importance of prenatal education and are often ignored. There are even people who think that educating children begins after the child is born. This assumption is a big mistake because educating children from birth is a very important thing in the form of indirect stimuli or touches, both in physical and psychological form. Providing this kind of stimulation can be an education in itself for the fetus in the womb.